Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan: Studi Pada Salah Satu Perusahaan Vendor Alat Telekomuniasi di Kota Bandung - Mochamad Saeful Taufik; Senen Machmud; Vicky Achmad Zulfikar; Dhea Perdana Coenraad (Jurnal Computech & Bisnis (e-journal), 2022)
Motivation and work discipline are several factors that can affect employee performance; therefore, this study aims to examine motivation and work discipline on employee performance at one of the telecommunications equipment vendors in Bandung. Sources of data used in this study are primary data in the form of questions (questionnaires) which shows to employees of telecommunications equipment vendor companies in the city of Bandung. The respondents used in this study used a population of 65 people or respondents. Statistical methods used in this research are descriptive and verification methods. The results of this study indicate that all independent variables, namely, motivation and work discipline, positively influence the dependent variable, namely, employee performance. Motivation has a total effect of 36.96%, consisting of a direct influence of 21.97% and an indirect influence through work discipline of 14.99%. Work discipline has a total effect of 28.74%, which consists of a direct effect of 13.84%. An indirect effect through the motivation of 14.99%, testing the coefficient of determination analysis shows that motivation and work discipline simultaneously affect performance by 65.7%. In comparison, at 34.3%, the rest can influence by other variables not examined in the study. The implications of the study recommend that companies improve employee performance. To achieve better work results, management should further improve employee work results and pay attention to employee work needs.